A ciência na Educação Infantil: uma análise a partir dos projetos e reflexões desenvolvidos por educadores infantis - Souza, Carolina Rodrigues de (Universidade Federal de São Carlos, 2008)
The current work (This present paper) aims to reflect how to think the natural sciences in the field of Child Education, since this science is related to a rigid knowledge corpus, structured and organized and the education in the childhood is associated to the child care perspective, also connected to looking after. To carry out this discussion we developed a approximation survey among with the child space, located in a child care institution EMEI, where we worked directly with all professionals in that institution who developed work projects focusing science. Following, we selected three out of them to participate in a confronting process and self-confronting. This method proposes a collection and analysis work from several perspectives, view that the descriptions and observations can bear different evolutions. This method also approaches the complexity of nature of the subjects' speech and actions and from these confrontations between subject versus researcher and among the subjects themselves, if seeks to provide reflections such as what I have done , what I should do and What I am going to do an brings more ethic and reliable data (Crindal Alain, 2005). With this propose we seek to analyze from projects and reflections developed by the child educators what science in child education means. Based upon the theoretical references discussed by the Psychology of Development and the Sociology of Childhood we found the pedagogical practices of those professionals and their respective conceptions about what a child is, to bear a childhood and the purpose of the child institution and the correlations among such theories, a back and forth movement of ideas (of preparing to) connected to the perspective of becoming and the social perspective of being today . Thus, we finish the paper outlining the importance of 'seeing' the child as a creator, capable to establish multiples relationships, a sociological-historical subject, builder of culture and within it, and by this perspective a work that values the science of child education, while life discovering, the world around child and not the science as a organized structure and structured, aiming an anticipation of schooling.
Keywords: Ensino de Ciências; Educação infantil; Sociologia da infância; CIENCIAS HUMANAS::EDUCACAO